Trial Steering Committees in randomised controlled trials: A survey of registered clinical trials units to establish current practice and experiences. (December 2015) - Conroy, Elizabeth J; Harman, Nicola L; Lane, J Athene; Lewis, Steff C; Murray, Gordon; Norrie, John; Sydes, Matt R; Gamble, Carrol
Background: The Medical Research Council Guidelines for Good Clinical Practice outlines a three-committee trial oversight structure – the day-to-day Trial Management Group, the Data Monitoring Committee and the Trial Steering Committee. In this model, the Trial Steering Committee is the executive committee that oversees the trial and considers the recommendations from the Data Monitoring Committee. There is yet to be in-depth consideration establishing the Trial Steering Committee's role and functionality. Methods: A survey to establish Trial Steering Committee's current practices, role and the use and opinion on the Medical Research Council guidelines was undertaken within UK Clinical Research Collaborative registered Clinical Trials Units. Results: Completed surveys were obtained from 38 of 47 fully and partially registered Units. Individual items in the survey were analysed and reported spanning current Trial Steering Committee practices including its role, requirement and experience required for membership; methods to identify members; and meeting frequency. Terms (a document describing the committee's remit, objectives and functionality) were obtained and analysed from 21 of 33 Units with documents in place at their Unit. A total of 20 responders suggested aspects of the current Medical Research Council Guidelines that need improvement. Conclusion: We present the first survey reporting on practices within UK Clinical Research Collaborative registered Clinical Trials Units on the experience and remits of Trial Steering Committees. We have identified a widespread adoption of Medical Research Council Guidelines for Trial Steering Committees in the United Kingdom, but limitations in this existing provision have been identified that need to be addressed.